DAMPAK KEPUASAAN KERJA SEBAGAI PEMEDIASI FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA KARYAWAN - Rachmawati Meita Oktaviani; Tjahjaning Poerwati (Jurnal Bisnis dan Ekonomi, 2017)
This study aims to factors that affect employee performance. This study also intends to test whether job satisfaction can mediate the relationship of role ambiguity and professional commitment to employee performance. This research is a quantitative research using survey model. Analysis technique used conviniance sampling with sample number 80 respondents who are employees of Public Accounting Firm in Semarang area. The results of the study are as follows: 1). Partial role ambiguity has no effect on job satisfaction and employee performance; 2). Commitment of the profession in a partial way affect the job satisfaction and employee performance, and 3). Job satisfaction affects employee performance. Based on path test results that have been done mention that job satisfaction does not successfully mediate relationship ambiguity role and professional commitment partially to employee performance. Keywords: Role ambiguity, professional commitment, job satisfaction, employee performance